(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
The article discusses the results of the tests carried out in practical form in which they were used to determine the specific mass of the grains (ρs) and the moisture content of a soil (ω), for this, through stages and laboratory methods, the soil behavior could be analyzed, thus being able to determine these respective values, in order to seek to understand some of the characteristics that the soil physically presents. To determine the specific mass of grains (ρs) of the soil sample, the method used was the test using the pycnometer method, defined by the Brazilian Regulatory Standard - ABNT NBR 6458, in its Annex B; and to determine the moisture content (ω), the test was performed through the greenhouse, following the Brazilian Regulatory Standard - ABNT NBR 6457, Annex A. Thus, it was possible to analyze with good reliability the results obtained in these trials, which through three achievements, especially because they were performed at different duration times, thus being possible to perceive that the values for these specific mass determinations of grains (ρs) and moisture content (ω), are practically the same, regardless of the time used in some stages or in the exclusion of some of them, being the amount of water, the factor directly linked to these characteristic points that were analyzed.